Coordinated control of a hybrid wind farm with PMSG and FSIG during asymmetrical grid fault. (February 2018) - Yao, Jun; Li, Jiawei; Guo, Lisha; Liu, Ruikuo; Xu, Depeng
Highlights: The coupling relationship between positive- and negative-sequence voltage is studied. The impact of operation behavior on the grid voltage components is analyzed. The impact of equivalent impedance on the grid voltage components is analyzed. A coordinated LVRT control strategy for the hybrid wind farm is presented. Abstract: This paper investigates a coordinated control of a hybrid wind farm with permanent magnet synchronous generator (PMSG)-based and fixed-speed induction generator (FSIG)-based wind turbines during asymmetrical grid fault. According to the boundary conditions of asymmetrical grid fault, the coupling relationship between positive- and negative-sequence grid voltages is presented in detail. Furthermore, the impact of the operation and equivalent impedance of the hybrid wind farm on the grid voltage components during asymmetrical grid fault are analyzed. A coordinated low voltage ride through (LVRT) control strategy for a hybrid wind farm without communication equipments is then developed based on the impact analysis. The proposed strategy supports the grid voltage recovery with the reactive power provided from the PMSG systems. Meanwhile, by using the extra current capacity of the PMSG systems to provide the negative-sequence current, the negative-sequence grid voltage can be suppressed. As a result, performance and output power quality of the FSIG-based wind farm are both improved with the coordinated control of PMSG-based wind farm. Finally, the simulation results of a hybrid wind farm under different asymmetrical grid fault conditions and a phase-phase short circuit fault experimental results of laboratory-scale test rig both validate the proposed coordinated control strategy.